Life cycle assessment and life cycle costing toward eco-efficiency concrete waste management in Malaysia - Mah, Chooi Mei (Elsevier Ltd, 2018)
The large amount of concrete waste (CW) generated during the construction and demolition stages and the improper management of it often results in considerable environmental impact. The main purpose of this study is to identify the most eco-efficiency scenario in CW management. The life cycle assessment (LCA) modelling is used to assess the environmental impact, GHG emissions and the life cycle cost (LCC) is used as an extension of LCA in the term of economic dimension. Decision making in waste management often come hand in hand with economic incentives. Aligning both LCA and LCC in environmental-cost effectiveness as the eco-efficiency analysis helps in measuring sustainability. Scenarios were built to access different CW options. Scenario 1 (S1) depicts the landfilling. Scenario 2, 3, and 4 (S2, S3, & S4) are the recycling scenario where CW is recycled into concrete aggregate (RCA) to substitute the natural aggregate (NA) in road construction and in recycled aggregate concrete (RAC) production. Results show that S3, recycling of CW to substitute NA in concrete production has the highest eco-efficiency of 1.72 while landfilling has the lowest eco-efficiency of 1.15. Higher eco-efficiency means lower environmental and cost impacts. CW is preferably uses as a substitution of the NA to reduce the need in mining of NA. This study also identified that transportation distances and mining activity are the main contributors to GHG emissions and cost impact. Sensitivity analysis evaluated the what-if scenario of building a mobile material recovery facilities (MRF) within 3 km from waste source site. The results show that the what-if scenario (S3’ with 1.78 eco-efficiency) could possibly reduces 50.8% GHG emissions and 68.1% of cost saving as compared to landfilling scenario.